2018
DOI: 10.1515/cclm-2018-0073
|View full text |Cite
|
Sign up to set email alerts
|

Indirect methods for reference interval determination – review and recommendations

Abstract: Reference intervals are a vital part of the information supplied by clinical laboratories to support interpretation of numerical pathology results such as are produced in clinical chemistry and hematology laboratories. The traditional method for establishing reference intervals, known as the direct approach, is based on collecting samples from members of a preselected reference population, making the measurements and then determining the intervals. An alternative approach is to perform analysis of results gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
202
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 210 publications
(205 citation statements)
references
References 40 publications
1
202
0
2
Order By: Relevance
“…In the indirect method, RIs can be calculated using various statistical approaches . Of these statistical approaches, the standard parametric or non‐parametric percentile approach is usually used in the direct method for RIs as described in the CLSI EP‐A3 guidelines .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the indirect method, RIs can be calculated using various statistical approaches . Of these statistical approaches, the standard parametric or non‐parametric percentile approach is usually used in the direct method for RIs as described in the CLSI EP‐A3 guidelines .…”
Section: Discussionmentioning
confidence: 99%
“…Of these statistical approaches, the standard parametric or non‐parametric percentile approach is usually used in the direct method for RIs as described in the CLSI EP‐A3 guidelines . Jones et al suggested that the standard parametric or non‐parametric statistical approach can be used in the indirect method for RIs when the data were collected at a community screening project or similar. In fact, the parametric approach has been used in the analysis of data from NHANES, and the non‐parametric approach has been used in a Chinese and a Turkish study, respectively .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Establishment of reference intervals by conventional means entails direct testing of specimens from a number of “healthy” individuals; in many cases, these may be preselected from a limited age range, socio‐economic status and ethnicity. More recently, indirect methods for setting reference intervals using an evaluation of patients’ data have been suggested as a better approach towards harmonisation of ranges . The use of harmonised reference intervals for key analytes such as Hb will not preclude the laboratory from producing local ranges for the purpose of validation but will be a driver for improved traceability of patients’ results to higher order reference materials and methods and potentially reduce the variability in the postanalytical phase.…”
Section: The Postanalytical Phase: From the Laboratory Bench To The Rmentioning
confidence: 99%